Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, Prashant K.; Ratha, Satyajit; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of a and beta-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of beta-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of alpha and beta-NiMoO4 at a base pressure of similar to 1 x 10(-8) mbar. The obtained turn-on field at emission current density of 1 mu A/cm(2) for beta-NiMoO4 nanosheets and alpha-NiMoO4 is 1.3V/mu m and 2.2V/mu m respectively were observed. The maximum field emission current density of 1.006 mA/cm(2) at an applied electric field of 2.7V/mu m was achieved for beta-NiMoO4 nanosheets. Furthermore, we found that the beta-NiMoO4 nanosheets possess good field emission performance compared to alpha-NiMoO4. The results indicate that NiMoO4 can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase. (C) 2017 Elsevier B.V. All rights reserved.